Ricci curvature of submanifolds in Kenmotsu space forms - Kadri Arslan; Ridvan Ezentas; Ion Mihai; Cengizhan Murathan; Cihan Özgür (International Journal of Mathematics and Mathematical Sciences)
In 1999, Chen established a sharp relationship between the Ricci curvature and the squared mean curvature for a submanifold in a Riemannian space form with arbitrary codimension. Similar problems for submanifolds in complex space forms were studied by Matsumoto et al. In this paper, we obtain sharp relationships between the Ricci curvature and the squared mean curvature for submanifolds in Kenmotsu space forms.